The use of body growth and kinship data from 16 generations for predicting Thoroughbred performance - Dall’Anese, Julia; da Silva Junior, Joaquim Dias Antunes; Abrahão, Carolina Lorena Hohl; Dias de Castro, Luciana Laitano; Brandão, Yara de Oliveira; Yoshitani, Úrsula Yaeko; Knopp, Vanessa; Molento, Marcelo Beltrão (Archives of Veterinary Science, 2023)
Thoroughbred horses have been intensely raised for their athletic potential that is correlated with morphological parameters (i.e., body weight - BW, and withers height - WH). Optimum and consistent body development is aimed, but excessive growth rates may lead to the development of orthopedic diseases. This study aimed to generate growth rate curves and prediction models of Thoroughbred horses by analyzing BW and WH data collected monthly over 16 years of 378 animals (23.6 animals/year). The animals were checked from birth to 18 months (160 colts and 181 fillies) on a farm in the south of Brazil. A prediction performance ARIMA model was developed based on the BW and WH of the foals using a maximum and minimum range of 7320 observations. BW and WH were 54,1 kg and 102,5 cm at birth and 397,8 kg and 150,6 cm at 18 months of age, respectively. No differences were found between sex at any age. Moreover, we have established a nonlinear function for the growth curve and on average, foals were expected to get 7.4 times heavier and 1.5 times taller when animals were fully grown. Males showed greater BW uniformity than females, as females had a lower minimum BW than males. Significant statistical differences (P < 0,05%) were reported for BW and WH of foals between pairs of sires highlighting the kinship (paternal) effect on the animals’ development. Seventy-two pairs of stallions showed statistical relevance for BW and 91 for WH. The ARIMA model produced a linear trend of BW and WH for the forecasted years. In conclusion, we recommend that careful sire selection and adequate health (i.e., parasite control, vaccination), and nutrition strategies must be adopted to achieve superior body growth as estimated by the predicting model (positive scenario). The present protocol shall be used in studs worldwide to monitor horse development. The spreadsheet is available on request to the corresponding authors.